Insights into the positive effects of power ultrasound on the pore solution of Portland cement pastes. (January 2022) - Ehsani, Ahmad; Ganjian, Eshmaiel; Mason, Timothy J.; Tyrer, Mark; Bateman, Mark
Abstract: The influence of the direct application of power ultrasound (PUS) at several frequencies and power densities to Portland cement (PC) pastes is investigated in detail. Two PC pastes at water-to-cement ratios of 0.50 and 0.80 were studied. The composition of the pore solution and hydrates after introducing PUS irradiation for various periods were examined using ICP-OES, X-ray diffraction (XRD) and thermogravimetric analysis (TGA) techniques. The results indicate for the first time that applied PUS used in this study, can disturb the early formation of ettringite whilst appreciably promoting the formation of amorphous aluminium hydroxide hydrate by considerably releasing the aluminium ions into the pore solution. Moreover, PUS can increase carbonates by intensifying the carbonation in the PC systems particularly the system with higher water content. The present research concludes that ultrasound could be a promising technique to enhance ternesite hydration in ternesite-rich belitic calcium sulphoaluminate cements.